Chemical parameter optimization of cellulase production by Aspergillus niger on solid state fermentation of sugarcane bagasse - Muhammad Lokman, Muhammad Ramdan (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.